Upaya Meningkatkan Keterampilan Menulis Teks Ilmiah melalui Teknik Parafrase Siswa Kelas VIII di SMP Negeri 10 Madiun - Firmansyah, Syafiul Ardi; Samsiyah, Nur; Astuti, Roro Tri (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
This study aims to improve scientific writing skills and reduce plagiarism among eighth-grade students through the application of paraphrasing techniques. The research employed a Classroom Action Research (CAR) approach using the spiral model developed by Kemmis and Taggart, implemented over two cycles. The subject of the study was Class VIII A of SMP Negeri 10 Madiun, consisting of 35 students. Each cycle consisted of the stages of planning, action, observation, and reflection. The results showed that prior to the implementation of the paraphrasing technique (pre-cycle), students’ writing skills were categorized as poor, with an average score below 70 and a plagiarism rate exceeding 50%. In the first cycle, a notable improvement was observed; the average writing score rose above 70, and the plagiarism rate dropped to around 50%. Further improvement occurred in the second cycle, where the average score exceeded 80 and the plagiarism rate decreased to a maximum of 20%. These findings indicate that the paraphrasing technique is effective in enhancing scientific writing skills and minimizing plagiarism among junior high school students.